KELIMPAHAN FITOPLANKTON DI PERAIRAN MAITARA, KOTA TIDORE KEPULAUAN - Yuliana Yuliana (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of this research were to know the correlation between water physic-chemistry and the abundance of phytoplankton. The studies were conducted from May to September 2006 at Maitara water and samples were taken from 5 (five) stations for 4 (four) period by filtration method. The result showed that there were 12 genera of phytoplankton from 4 classes: Bacillariophyceae (7 genera), Chlorophyceae (1 genera), Cyanophyceae (1 genera), and Dinophyceae (3 genera). The phytoplankton abundance ranged from 5781 – 39227 individual/L, the highest value was on station 5 period III (39227 individual/L) and the lowest on station 3 period IV (5781 individual/L). The range values of phytoplankton biological index such as diversity index (H’) was 0.6889 – 1.1841, equitability index (E) = 0.4969 – 0.7215, and dominant index (D) = 0.3856 – 0.6183. Physical-chemistry parameters of the water were 0.01 – 2.24 mg/L of nitrate, 0.09 – 0.28 mg/L of orthophosphate, 0.040 – 0.042 of silicate, 6.21 – 8.27 of pH, 30 – 35 ‰ of salinity, 28.4 – 31.5oC of temperature, and 1.10 – 2.75 m of transparency, respectively. Multiple regression analysis showed that there was relationship between waters physical-chemistry parameters and phytoplankton abundance (R2 = 0.796), where the regression equation was Y = 150190.2 + 36.589 nitrate + 597.043 orthophosphate + 1002598 silicate + 25.289 pH - 23.866 salinity – 561.222 temperature – 56.973 transparency.